Riluzole But Not Melatonin Ameliorates Acute Motor Neuron Degeneration and Moderately Inhibits SOD1-Mediated Excitotoxicity Induced Disrupted Mitochondrial Ca2+ Signaling in Amyotrophic Lateral Sclerosis - Jaiswal, Manoj Kumar (Frontiers in Cellular Neuroscience, 2017)
Selective motoneurons (MNs) degeneration in the brain stem, hypoglossal motoneurons (HMNs), and the spinal cord resulting in patients paralysis and eventual death are prominent features of amyotrophic lateral sclerosis (ALS). Previous studies have suggested that mitochondrial respiratory impairment, low Ca2+ buffering and homeostasis and excitotoxicity are the pathological phenotypes found in mice, and cell culture models of familial ALS (fALS) linked with Cu/Zn-superoxide dismutase 1 (SOD1) mutation. In our study, we aimed to understand the impact of riluzole and melatonin on excitotoxicity, neuronal protection and Ca2+ signaling in individual HMNs ex vivo in symptomatic adult ALS mouse brain stem slice preparations and in WT and SOD1-G93A transfected SH-SY5Y neuroblastoma cell line using fluorescence microscopy, calcium imaging with high speed charged coupled device camera, together with immunohistochemistry, cell survival assay and histology. In our experiments, riluzole but not melatonin ameliorates MNs degeneration and moderately inhibit excitotoxicity and cell death in SH-SY5YWT or SH-SY5YG93A cell lines induced by complex IV blocker sodium azide. In brain stem slice preparations, riluzole significantly inhibit HMNs cell death induced by inhibiting the mitochondrial electron transport chain by Na-azide. In the HMNs of brainstem slice prepared from adult (14–15 weeks) WT, and corresponding symptomatic SOD1G93A mice, we measured the effect of riluzole and melatonin on [Ca2+]i using fura-2 AM ratiometric calcium imaging in individual MNs. Riluzole caused a significant decrease in [Ca2+]i transients and reversibly inhibited [Ca2+]i transients in Fura-2 AM loaded HMNs exposed to Na-azide in adult symptomatic SOD1G93A mice. On the contrary, melatonin failed to show similar effects in the HMNs of WT and SOD1G93A mice. Intrinsic nicotinamide adenine dinucleotide (NADH) fluorescence, an indicator of mitochondrial metabolism and health in MNs, showed enhanced intrinsic NADH fluorescence in HMNs in presence of riluzole when respiratory chain activity was inhibited by Na-azide. Riluzole’s inhibition of excitability and Ca2+ signaling may be due to its multiple effects on cellular function of mitochondria. Therefore formulating a drug therapy to stabilize mitochondria-related signaling pathways using riluzole might be a valuable approach for cell death protection in ALS. Taken together, the pharmacological profiles of the riluzole and melatonin strengthen the case that riluzole indeed can be used as a therapeutic agent in ALS whereas claims of the efficacy of melatonin alone need further investigation as it fail to show significant neuroprotection efficacy.